[The Marginalist Principle in a Discrete Production Model Under Uncertain Demand]: Rejoinder - Fei, J. C. H. (Quarterly Journal of Economics, 1971)
Journal Article Per Capita Consumption and Growth: Rejoinder Get access J. C. H. Fei J. C. H. Fei Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 85, Issue 4, November 1971, Pages 710–711, https://doi.org/10.2307/1882275 Published: 01 November 1971